Diversifying science: comparing the benefits of citizen science with the benefits of bringing more women into science. - Schroeder, S. Andrew (Synthese, 2022)
I compare two different arguments for the importance of bringing new voices into science: arguments for increasing the representation of women, and arguments for the inclusion of the public, or for “citizen science”. I suggest that in each case, diversifying science can improve the quality of scientific results in three distinct ways: epistemically, ethically, and politically. In the first two respects, the mechanisms are essentially the same. In the third respect, the mechanisms are importantly different. Though this might appear to suggest a broad similarity between the cases, I show that the analysis reveals an important respect in which efforts to include the public are more complex. With citizen science programs, unlike with efforts to bring more women into science, the three types of improvement are often in conflict with one another: improvements along one dimension may come at a cost on another dimension, suggesting difficult trade-offs may need to be made.